Beginning Java and Flex - Pisa, Filippo di (Apress, 2012)
Over the past few years, the now open source Adobe Flex Framework has been adopted by the Java community as the preferred framework for Java RIAs using Flash for the presentation layer. Flex helps Java developers build and maintain expressive web and desktop applications that deploy consistently on most web browsers and a growing number of mobile devices. Beginning Java and Flex describes new, simpler, and faster ways to develop enterprise RIAs. This book is not only for Java or Flex developers but for all web developers who want to increase their productivity and the quality of their development. In this book I will show you how to develop using the most popular Java lightweight frameworks such as Spring and Hibernate, using Flex and ActionScript 3 as the view layer. Once you have mastered this new development frontier, including concepts like Dependency Injection (DI) and Object Relationship Management (ORM), you will very likely want to use them for all your projects. Flex and Java are becoming very popular for both business and interactive applications, and they can open doors to the different branches of software development such as gaming, finance, advertising, and desktop applications of all kinds.